Sufis and Women: The Study of Women's Sufis in The Western World - Ariani Barroroh Baried; A. Hanief Saha Ghafur; Mulawarman Hannase (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The lack of records about the involvement and contribution of women in Sufism texts cannot be used as an excuse that women have a small role and position in the development and dissemination of Sufism teachings, doctrines and practices. So far, the well-known female Sufis, namely Rabi'ah al-Adawiyah (717-801) and Aishah al-Ba'uniyyah (c. 1456-1517), are two big names who prove that women have equal opportunities in spiritual attainment. Many researchers discuss female Sufis but focus on the eastern world and parts of India, only a few researchers have written about female Sufis in the West, therefore the authors are interested in discussing female Sufis in the West. This research is a library research. The author uses a literature review with the data sources used in this paper are secondary data originating from the literature such as books, journals, articles, and various sources that are relevant to the theme of the discussion in this paper.. The results of the study describe female Sufisin the contemporary era such as Hajjah Amina Adil and Hajjah Naziha Adil with their organizations engaged in philanthropy. Then another female Sufi is Nahid Angha who is known as one of the founders of the International Sufi Woman Organization, a world Sufi women's organization. This organization is concerned with peace programs and women's empowerment.The next female Sufi, namely Eva de Vitray in the path of Sufism, Eva de Vitray-Meyerovitch or Hawwa Hanim, took allegiance to the murshid of the Qadiriyah order from Morocco, Sheikh Hamzah al-Qadiri al-Boutchichi. Eva is also connected with Sheikh Khaled Bentounes, a murshid of the Syadziliyah-Alawiyahtarekat who lives in France